Outcomes and prognostic factors in thyroid cancer patients with cranial metastases: A retrospective cohort study of 4, 683 patients. (July 2018) - Hong, Yi-Wen; Lin, Jen-Der; Yu, Ming-Chin; Hsu, Chih-Chieh; Lin, Yann-Sheng
Abstract: Background: Cranial metastasis of thyroid cancer is rare. The aim of this study was to analyse the clinical characteristics, treatments and outcomes of thyroid cancer patients with cranial metastasis and to identify the associated prognostic factors. Materials and methods: Between January 1977 and August 2017, a total of 4683 patients were histologically confirmed to have thyroid cancer. Among them, 25 patients (0.53%) were identified as having cranial metastases, and their medical records were reviewed. The Kaplan-Meier method with a log-rank test was performed with cancer-specific survival as the main outcome. Cox regression analysis was used to examine the potential prognostic factors influencing patient survival. Results: Of the 25 patients, 21 were female, and 4 were male. The median age at the time of diagnosis of cranial metastasis was 63 years. Sixteen patients had metastases to the brain, and nine patients had metastases involving the skull only. Papillary carcinoma and follicular carcinoma accounted for 84.0% of cases. Twenty-four cases (96.0%) had extracranial metastases at the time of diagnosis of cranial metastases. Twenty patients received surgery, and 4 patients received palliative radiotherapy. One patient received supportive care only. The median cancer-specific survival after the diagnosis of cranial metastases was 27 months. According to the Kaplan-Meier test, 3 factors had a significant impact on survival, the metastatic site, histological types and surgical resection. According to the Cox regression analysis, skull metastases (HR: 0.274, 95% CI: 0.083–0.904, p = 0.033) and surgical resection (HR: 0.134, 95% CI: 0.019–0.929, p = 0.042) were identified as independent prognostic factors for a better outcome. Conclusions: Surgical resection is the mainstay therapy for thyroid cancer patients with cranial metastasis. Cranial metastases involving the skull only are associated with a better outcome. Highlights: The overall incidence of cranial metastases from thyroid cancer was 0.53%. Well-differentiated thyroid carcinoma accounted for 84.0% of cases. Twenty-four cases (96.0%) had co-existing extracranial metastases at the time of diagnosis of cranial metastases. Surgical resection is the mainstay therapy for thyroid cancer patients with cranial metastasis. Cranial metastases involving the skull only are associated with a better outcome.